Saddle and Tack Care in Hot and Humid Environments - Joel McQuagge; Todd Thrift; Ed Johnson (EDIS, 2014)
The South’s climate is appealing for equestrian activities. While riders enjoy the weather, it creates some challenges in caring for saddles and other tack. When the weather becomes hot and the humidity climbs and the rains are frequent, a tack room can become a breeding ground for mold and mildew. There are several things a rider can do, however, to lower the incidence of mildew on saddles and tack. This 3-page fact sheet was written by Joel McQuagge, Todd Thrift, and Ed Johnson, and published by the UF Department of Animal Sciences, November 2014. (Photo credit: Joel McQuagge, UF/IFAS)